The leadership of madrasah principals as change agents in the educational management reform of the merdeka curriculum - Achmad Syakur (Yayasan Azhar Amanaa Yogyakarta, 2025)
The leadership of madrasah principals plays a strategic role as change agents in implementing educational management reforms, particularly in the context of the Merdeka Curriculum. This study aims to analyze how madrasah principals initiate, direct, and oversee managerial transformations to ground the principles of the Merdeka Curriculum within the madrasah environment. Using a qualitative-descriptive approach, data was collected through in-depth interviews, participatory observations, and documentation studies in several madrasahs that served as research samples. The results indicate that the transformative leadership of madrasah principals, which is adaptive, collaborative, and visionary, is key in building a free and participatory learning culture. The madrasah principal acts as a facilitator of change, a driver of learning innovation, and a strengthening force in madrasah governance based on the values of moderation and progress. These findings recommend the importance of strengthening the leadership capacity of madrasah principals through continuous training and policy mentoring to effectively and sustainably manage curriculum change dynamics. This article uses a library research method with a descriptive-qualitative approach and thematic analysis to explore the strategic role of madrasah principals as change agents in the implementation of the Merdeka Curriculum. The study is conducted by reviewing relevant literature to identify patterns, concepts, and challenges in transformative leadership and managerial strategies within the context of educational reform in madrasahs. The study results show that madrasah principals play a central role as change agents in the educational management reform based on the Merdeka Curriculum. The transformative and participatory leadership applied includes strengthening planning, developing contextual curricula, managing human resources, and integrating technology. Despite facing structural and cultural challenges, madrasah principals are able to overcome obstacles through effective communication, empowering teachers, and creating an adaptive learning ecosystem to ensure relevant and sustainable educational quality.